Fluid flow impacts endothelial-monocyte interactions in a model of vascular inflammatory fibrosis - Isabelle Linares; Kaihua Chen; Ava Saffren; Mehran Mansouri; Vinay V. Abhyankar; Benjamin L. Miller; Stefano Begolo; Hani A. Awad; James L. McGrath (Scientific Reports)
Abstract The aberrant vascular response associated with tendon injury results in circulating immune cell infiltration and a chronic inflammatory feedback loop leading to poor healing outcomes. Studying this dysregulated tendon repair response in human pathophysiology has been historically challenging due to the reliance on animal models. To address this, our group developed the human tendon-on-a-chip (hToC) to model cellular interactions in the injured tendon microenvironment; however, this model lacked the key element of physiological flow in the vascular compartment. Here, we leveraged the modularity of our platform to create a fluidic hToC that enables the study of circulating immune cell and vascular crosstalk in a tendon injury model. Under physiological shear stress consistent with postcapillary venules, we found a significant increase in the endothelial leukocyte activation marker intercellular adhesion molecule 1 (ICAM-1), as well as enhanced adhesion and transmigration of circulating monocytes across the endothelial barrier. The addition of tissue macrophages to the tendon compartment further increased the degree of circulating monocyte infiltration into the tissue matrix. Our findings demonstrate the importance of adding physiological flow to the human tendon-on-a-chip, and more generally, the significance of flow for modeling immune cell interactions in tissue inflammation and disease.